The Teacher's Role in Forming Student Discipline Character in Elementary Schools - Rafif, Adika; Dafit, Febrina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the teacher's role in forming the disciplinary character of fourth-grade students at SD Negeri 112 Pekanbaru. This research is qualitative research with a case study model. The research data is the teacher's role in shaping the disciplinary character of students, while the data source in this study is the results of observations at SDN 112 Pekanbaru. Data collection techniques are in the form of interviews, observation, and documentation. Data analysis uses the Milles and Huberman model with three stages, namely data reduction, data presentation, and conclusion. The results of the study show that the teacher's role in shaping the character of student discipline at SDN 112 Pekanbaru is to reinforce the value of obedience by giving examples such as coming to school on time and complying with school rules and regulations. The value of the order is carried out by accustoming students to maintain calm and cleanliness in the class. The value of the order is carried out by accustoming students to dress neatly, cleanly and submit assignments on time. Compliance value in which the teacher gives sanctions when students cannot comply with and implement existing regulations. The value of loyalty to students is carried out by reminding students of the lecture method, and the teacher also plays a role in motivating students to be better and still giving sanctions when students cannot carry out the agreements that have been made.